Study of Response Spectra for Ulaanbaatar city - Amarsanaa, Munkhsaikhan; Chimed, Odonbaatar; Munkhjargal, Dembereldulam; Erdene, Ganzorig (Proceedings of the Mongolian Academy of Sciences, 2022)
According to researchers, Ulaanbaatar, the capital city of Mongolia, is in an active seismic zone, and more active faults around the city have been discovered in the last few decades. This is an alarming news for the city that has been expanding and developing rapidly. Therefore, consideration of the construction of structures that can withstand strong earthquakes has been becoming a complex problem from economic perspective and urban planning. This study aims to develop response spectra for all and any structure constructs in the city. To complete this requirement, we generated maximum response spectra correlating different soil classes, and taking into considering all potential active sources around the city. In this research work, we have proposed various response spectra that are associated with five different soil classes, and these response spectra can be used for the city.